ANALISIS KINERJA DINAS LINGKUNGAN HIDUP KABUPATEN BENGKALIS DALAM MENGATASI PERMASALAHAN LIMBAH CAIR KELAPA SAWIT DI KECAMATAN MANDAU TAHUN 2022 - Nugroho, Feri; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the performance of the Environmental Agency (DLH) of Bengkalis Regency in addressing the issue of palm oil liquid waste in Mandau District. The research employs a descriptive qualitative approach, with data collected through interviews, documentation, and literature review. The results indicate that the performance of DLH has not been optimal, even though the Environmental Quality Index (IKLH) achievement reached 93.96% of the target. The main challenges include limited budget, lack of experts, and insufficient time to respond to public complaints. Improvement efforts such as strengthening the monitoring system, enhancing staff competencies, and efficient budget management are urgently needed to increase the effectiveness of palm oil waste control. Keywords: Performance, nvironmental Agency, Liquid Waste, Palm Oil, Monitoring, Mandau District